László Teleki, the diplomat of the Hungarian war of independence - Miru, György (Acta Neerlandica, 2020)
This paper gives an overview of the political career of László Teleki, the leading diplomat of the Hungarian war of independence. Based on the topics discussed in this volume, his efforts as a writer of literature will also be mentioned here, though his theatrical pieces met just modest popular acclaim. Teleki joined politics, and became a well-known and successful politician in support of reformists. Later, before the war with Austria, he was appointed to act as the ambassador of the independent Hungarian government to Paris. He had a key role in shaping Hungarian foreign policy, wanted to secure the independence of the country both during the war of independence and in emigration. This paper focuses on this latter period, when his correspondence clearly reflected his political commitment and approach, as well as changes in his personal relations.